Effects of underlying substrates on the underwater oleophobicity of graphene oxide-phytic acid (GO-PA) coatings - Sue Lyn Tan; Abraham Matthews Joshua; Ee Von Lau (Results in Engineering)
The widespread presence of oil in aquatic environments due to indiscriminate disposal of oily wastewater and frequent oil spills has led to severe underwater oil adhesion issues. While underwater oleophobicity has received extensive research for its potential to create surfaces with ultralow oil adhesion underwater, there are still limited studies on the effects of underlying substrates on surface wettability. This study addresses this gap by exploring the wettability of graphene oxide-phytic acid (GO-PA) coatings on different substrates, which is crucial given the dependency of two-dimensional materials such as graphene oxide, on the underlying substrates due to their inherent lack of a bulk phase. The GO-PA coatings were applied on a variety of substrates, and their surface wettability was evaluated through contact angle measurements, surface energy calculations and adhesion force studies. Results showed that the underwater oleophobicity of GO-PA coated substrates was the lowest in stainless steel, followed by copper, polyvinylidene fluoride (PVDF) and carbon steel. The underwater oleophobicity was correlated to the increase in surface energy and surface roughness, accompanied by a reduction in the water de-wetting phenomenon at the contact region. Notably, carbon steel exhibiting the highest surface energy (72.8 mJ/m2) and surface roughness (average roughness of 146.0 nm), emerged as the most effective substrate for developing surfaces with superhydrophilicity (water contact angle of 0°) and underwater superoleophobicity (underwater oil contact angle of 162.5°). This research establishes a promising avenue for further developing modified GO coatings aimed at anti-oil applications such as oily wastewater treatment and wax prevention.